Analisis Pengembangan Media Pembelajaran Sederhana Pada Sekolah Dasar - Zaza Salsabila; Vira Eka Putri; Rara Salsabila; Wismanto Wismanto; Pahruddin Pahruddin (Lembaga Pengembangan Kinerja Dosen, 2024)
In the learning process, of course it will be carried out well depending on how the teacher plans learning activities. The presence of learning media will have an important influence on the implementation of learning and this learning media will become an effective tool or dependent media and will be able to become teaching material that can be used by students, process learning will not be able to take place well without the development of learning media, usually often facing several obstacles, one of which is that facilities and infrastructure are still lacking, for example there is no learning media that supports the continuity of the learning process, learning media includes a sense that is physically used in providing material content. , which comes from frame images, graphs, cassettes, books, video recorders, tape recorders, pictures, video cameras, films, photos, television and computers. Media is a component of learning resources whose contents are instructional material in the student.